2023
DOI: 10.59952/tuj.v5i3.259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Scanning on the Performance of Small and Medium Manufacturing Enterprises in Kenya

Karimi Sekere

Abstract: This paper addresses the Influence of Environmental Scanning on the Performance of Small and Medium Manufacturing Enterprises in Kenya. Methodically, the study was guided by the positivism research philosophy. The study applied cross-sectional descriptive research design since data collection in this study was carried out in a structured inexpensive and minimal time-consuming manner, assisting in answering the when, who, where, what and how questions and also determine whether a relationship exists between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Findings contributed that process innovation is a necessary mechanism to translate environmental scanning information to enhance resilience. Also, Sekere, Kiriri & Njenga (2023) in their study concluded that environmental scanning significantly influences performance of Small and Medium Manufacturing Enterprises. So, the managers and owners of the SMEs should develop an awareness of their industry and competitors, and consequently scan the environment regularly.…”
Section: Pourmohammadi Et Al (2020) Conducted Comprehensive Strategic...mentioning
confidence: 99%
“…Findings contributed that process innovation is a necessary mechanism to translate environmental scanning information to enhance resilience. Also, Sekere, Kiriri & Njenga (2023) in their study concluded that environmental scanning significantly influences performance of Small and Medium Manufacturing Enterprises. So, the managers and owners of the SMEs should develop an awareness of their industry and competitors, and consequently scan the environment regularly.…”
Section: Pourmohammadi Et Al (2020) Conducted Comprehensive Strategic...mentioning
confidence: 99%